Scientific Critical Thinking Model to Improve Scientific Literacy and Self-Regulation Skills in Buffer Solution Learning - Rusmansyah, Rusmansyah; Effendi, Akhmad Maulana; Mahdian, Mahdian; Aufa, Mohamad Nor (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
The low inputs, processes, and learning outputs require competency assessments in science, one of which is scientific literacy and self-regulation. This study aims to determine the differences in scientific literacy and self-regulation of students in buffer solution materials. This study is quasi-experimental using a non-equivalent control group design. The study population consisted of 205 students from the XI MIPA SMAN 7 Banjarmasin class, and sampling used purposive sampling techniques with a sample of 69 students. Data collection was carried out using test instruments in the form of multiple-choice Three Tier Tests and non-tests in the form of self-regulation questionnaires. The collected data were analyzed using Multivariate Variance Analysis (MANOVA) with the help of SPSS 27.0 software. The results of hypothesis testing show a significance of <0.05, meaning that there is a significant influence of critical thinking models on these two variables. So, it can be concluded that there is an influence of scientific critical thinking models on scientific literacy abilities and students' self-regulation.